Panoramic Radiography Measurements Not Correlated with BMD Results in End-stage Chronic Kidney Disease Patients - Ni'ami, Muhamad Aufa; Ferriastuti, Widiana; Rahardjo, Paulus (Global Medical & Health Communication (GMHC), 2025)
Chronic kidney disease (CKD) is a disorder of the kidney defined by a glomerular filtration rate of less than 60 ml/min/1.73 m2 for a minimum of three months, progressive and irreversible. One complication is chronic kidney disease-metabolic bone disorders (CKD-MBD), which can cause osteoporosis. This is diagnosed using bone mineral densitometry-dual energy absorptiometry (BMD-DXA) and panoramic radiographs, which can also detect thinning of the mandibular cortex in patients with CKD. This study aims to determine the correlation between osteoporosis images on panoramic photos with the results of lumbar and hip areal T-scores in chronic kidney disease (CKD). This research is an observational study with a prospective approach and cross-sectional design. The subjects of this study were 52 patients with chronic kidney disease (CKD). Undergoing hemodyalize procedure (HD) at Dr. Soetomo General Hospital for February–March 2024. Data was collected by taking the results of the panoramic photo examination and BMD-DXA to see the results of the T-score in each patient—data analysis using the Spearman test on SPSS software. Which resulted in the p-values for the panoramic mandibular index (PMI), mandibular cortical width (MCW), and mandibular cortical index (MCI) with a lumbar T-score range of 0.093 to 0.676 and the PMI, MCW, and MCI with left-right hip T-score, the p-values ranged from 0.318 to 0.970 (all p-values >0.05). It can be concluded that there is no correlation between the results of the T-score for the lumbar and hip regions and the measurements of PMI, MCW, and MCI. Therefore, employing these three measurements as a standard for osteoporosis screening using panoramic x-rays is not feasible.